The creation of temporal structures in graphic novels as represented by The Sandman by Neil Gaiman - Sadowska-Dobrowolska, Katarzyna (Papers in Linguistics, 2024)
Time is a complex structural element of the narrative which consists of the fabula time (story duration and order), the arrangement of events and the pace of action. In graphic novels, temporality of the story is created not only verbally – the iconic layer is also used to anchor the temporal aspect in individual frames. The article describes methods of creating time structures and anchoring time frames in individual panels of Neil Gaiman’s The Sandman. The undertaken research aims at attempting to describe temporal features most often expressed iconically or verbally. The analyses employed methods of describing verbal messages (componential and formal-semantic analysis) and qualitative semiotic analysis, typical of the description of multimodal messages. They showed regularities in the way of expressing temporality. Verbal indicators of time dominate in the creation of the linear scheme and the sequence of events (retrospection and anticipation). The paratactic pattern of events also requires verbal explanations of the iconic layer. The iconic creation of the temporal dimension of the plot dominates in the case of building the pace of action and signaling its changes, and in creating a simultaneous pattern. In addition, the graphic layer is responsible for the visual anchoring of the plot in particular time frames.